PENGARUH MODEL STAD TERHADAP HASIL BELAJAR MATEMATIKA KELAS V SDN 03 PONTIANAK KOTA - Walijah, Siti; Margiati, Margiati; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to analyze and prove the influence of the implementation of student team achievement division model on the results of learning mathematics class V SDN 03 Pontianak City. The research method used is experimental method with quasi experimental research and design type nonequivalent control group design. The population is all students of class V SDN 03 Pontianak City amounting to 117 people. The sample in this research were 24 students of classVB (control class) and 32students of classVC(experimental class). Data collection techniques used are measurement techniques with data collection tools in the form of student learning outcomes in the form of stuffing that amounted to 4 questions with 30 columns of stuffing. The research showed that the average post-test control class isÂ  60.58 and the mean post-test experimental class is 71,94. The result of t- test got thitung3,5429 amounted to 1,6749 and ttabel (Î± = 5% with dk = 54) that is meant thitung (3,5429) > ttabel (1,6749), so Ha is received. So, it can be concluded that there is influence of the implementation of student team achievement division model on mathematics learning outcomes of students class V SDN 03 Pontianak City. The counting of effect size, got ES amounted is 0,8 that belong to the high criteria.Â Keywords: Student Team Achievement DivisionModel, Learning Outcomes, Mathematic